The Bark of the Spruce Picea jezoensis Is a Rich Source of Stilbenes - Andrey R. Suprun; Alexandra S. Dubrovina; Olga A. Aleynova; Konstantin V. Kiselev (Metabolites, 2021)
Stilbenes are plant phenolic secondary metabolites that show beneficial effects on human health and possess high antifungal activity against plant pathogens. Currently, a search for plant sources with high stilbene levels is relevant, since stilbene content in various plant species can vary substantially and is often at a low level. In this paper, the bark and wood of Picea jezoensis were analyzed for the content and composition of stilbenes and compared with other known stilbene sources. The HPLC-MS analysis of P. jezoensis bark and wood extracted with different solvents and at different temperatures revealed the presence of 11 and 5 stilbenes, respectively. The highest number of stilbenes of 171 and 229 mg per g of the dry weight (mg/g DW) was extracted from the bark of P. jezoensis using methanol or ethanol at 60 °C for 2 h. Trans-astringin, trans-piceid, and trans-isorhapontin prevailed over other stilbenoids (99% of all detected stilbenes). The most abundant stilbene was trans-isorhapontin, reaching 217 mg/g DW or 87% of all stilbenes. An increase in the extraction time from 2 to 6 h did not considerably increase the detected level of stilbenes, while lower extraction temperatures (20 and 40 °C) significantly lowered stilbene yield. The content of stilbenes in the P. jezoensis bark considerably exceeded stilbene levels in other stilbene-producing plant species. The present data revealed that the bark of P. jezoensis is a rich source of stilbenes (primarily trans-isorhapontin) and provided effective stilbene extraction procedures.